An investigation of risk factors for symptomatic osteoarthritis of the knee in women using a life course approach. Issue 10 (22nd October 2003) - Dawson, J; Juszczak, E; Thorogood, M; Marks, S-A; Dodd, C; Fitzpatrick, R
Abstract : Study objective: To explore risk factors for symptomatic knee osteoarthritis (OAK) in women, which included wearing high heeled shoes. Design: Matched case-control study. Exposure information obtained by interview, included details about past footwear. Self reported weight and height data obtained representing when women left school, were aged 36–40 and were aged 51–55. Regular work activities (including periods when homemaker or carer), smoking, and hormone related data gathered using a life-grid. Setting: Interviews in participants' homes. Cases identified from orthopaedic hospital surgical waiting list, controls identified by general practitioners (GPs) Participants: Women aged 50 to 70 years. Cases awaiting knee replacement surgery. Controls, who had no past knee surgery and no knee pain in the past three years, were matched for age and GP. Altogether 111 eligible women were interviewed (29 cases, 82 controls). Main results: Univariate analyses identified several significant associations with OAK including past knee injury, arthritis of the feet, heavy smoking, being overweight (BMI 25 or above) and various occupational activities. Virtually all measures of high heeled shoes use were associated with reduced risk of OAK, although none of these findings were statistically significant. In multivariate analysis only BMI 25 or above at age 36–40 remained significantly associated with OAK (OR 36.4, 95% CI 3.07 to 432, p=0.004), although weak evidence suggested certain occupational activities might increase risk. Weight gain in early adult life was particularly pronounced among cases. Conclusions: Being overweight before the age of 40 considerably increased the risk of subsequent symptomatic OAK in women. Wearing high heeled shoes did not.